Multimodal critical discourse analysis of the cinematic representation of women as social actors - Bezerra, Fábio Alexandre Silva (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
In this paper, an expanded version of the visual social actor network (van Leeuwen 2008) is suggested in integration with the classifi cation of fi elds proposed by Martin (1992). In the context of multimodal critical discourse analysis, such network has provided a template for the discussion of the data aiming to reveal and interrogate the construal of women’s agency in the introductory part of the fi rst fi lm Sex and the City (2008). Overall results place women’s actions mostly in the private sphere but also reveal instances of gender performativity (Butler 1990) that question social norms for women mainly imposed by the media.